2020
DOI: 10.1186/s12889-020-09791-2
|View full text |Cite
|
Sign up to set email alerts
|

Burden of prediabetes, undiagnosed, and poorly or potentially sub-controlled diabetes: Lolland-Falster health study

Abstract: Background This study aimed to investigate prevalence and risk factors for prediabetes, undiagnosed diabetes mellitus, poorly and potentially sub-controlled diabetes in a rural-provincial general adult population in Denmark. Methods Using cross-sectional data from the Lolland-Falster Health Study, we examined a total of 10,895 individuals aged 20 years and above. Results Prevalence of prediabetes was 5.8% (men: 6.1%; women: 5.5%); of undiagnosed diabetes 0.8% (men: 1.0%; women: 0.5%); of poorly controlled di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The proportion of diabetes cases that were undiagnosed of 11% is low compared with previous reports of 22%–25%, 1–6 and far lower than IDF estimates from 2019 of 41% undiagnosed diabetes in Europe 7 . Nonetheless, several studies report declining proportions of undiagnosed diabetes, 2,4,24,25 and two population‐based studies from 2020 from Denmark and Greece found only 12% and 9% of patients with diabetes being undiagnosed, respectively 22,26 . In addition, a recent study from the UK Biobank found a similarly low prevalence of undiagnosed diabetes of 0.8% 23 …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The proportion of diabetes cases that were undiagnosed of 11% is low compared with previous reports of 22%–25%, 1–6 and far lower than IDF estimates from 2019 of 41% undiagnosed diabetes in Europe 7 . Nonetheless, several studies report declining proportions of undiagnosed diabetes, 2,4,24,25 and two population‐based studies from 2020 from Denmark and Greece found only 12% and 9% of patients with diabetes being undiagnosed, respectively 22,26 . In addition, a recent study from the UK Biobank found a similarly low prevalence of undiagnosed diabetes of 0.8% 23 …”
Section: Discussionmentioning
confidence: 67%
“…7 Nonetheless, several studies report declining proportions of undiagnosed diabetes, 2,4,24,25 and two population-based studies from 2020 from Denmark and Greece found only 12% and 9% of patients with diabetes being undiagnosed, respectively. 22 Prediabetes: HbA1c 39-47 mmol/mol (5.7%-6.4%) and no self report of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study population, the known prevalence of type 2 diabetes is also relatively high (2.9-6.4% [31] ), partly due to a large population of citizens of middle East origin at increased risk of type 2 diabetes [32] and a population of low socio-economic status. No current data are available on prediabetes in the studied area, but a recent study from a socio-economic comparable part of Denmark reported a prevalence of prediabetes of 5.8% and unknown diabetes of 0.8% [33] . As the prevalence of dysglycemia is high in our study compared to the background population, we find it of importance to screen patients with COVID-19 with HbA 1c at admission.…”
Section: Discussionmentioning
confidence: 96%
“…The control subjects were normotensive with a BMI of only 24.2 and thus less likely to have metabolic syndrome or T2D. Additionally, based on improved diagnostic activity over the last decade in Denmark the prevalence of non-diagnosed diabetes is low with estimated 0.6-0.8 % undiagnosed T2D patients in the aged 20-85 years (Jørgensen et al, 2020;Bruun-Rasmussen et al, 2020). Therefore, although not tested, cases of undiagnosed T2D in our control cohort is unlikely.…”
Section: Strengths and Limitationsmentioning
confidence: 99%